Science, Ghosts and Vision: Catherine Crowe's Bodies of Evidence and the Critique of Masculinity. (May 2014) - Heholt, Ruth
Abstract : This essay looks at the ghost tales of the prominent mid-Victorian spiritualist Catherine Crowe. In an early precursor to the Society for Psychical Research's 1895 'Census of Hallucinations', her most famous book The Night Side of Nature (1848) published people's tales of poltergeists, prophetic dreams, ghost sightings and uncanny coincidences through stories, anecdotes and reported personal experience. Crowe believed in the naturalness of the supernatural and her intention was to present the plethora of what she saw as 'evidence' to the scientific community for a hearing and as a starting place for examination. The body of evidence Crowe presented, however, was – far from being objective, distanced, testable or repeatable – subjective, personal, anecdotal and transient. Placing emphasis on intuition and experience, Crowe wanted science to look in a different way at psychic experiences, and to expand its narrow, supposedly rational and objective vision. Her tales look directly at white, upper-class Victorian men, and their bodies are presented for scrutiny as part of the evidence she wants (masculine) science to look at. This chapter argues that these ghost tales disrupt any narratives of unified, whole masculinity through the visibility and the presence of the male body and the questioning of science and rationality. Today, Crowe has fallen out of fashion; however, her work has proved to be prophetic in its concerns. This essay argues that in Crowe's own bodies of evidence, she blends the empirical and the spiritual, the objective and the subjective in a way that undermines the dominant certainties of science, empirical vision and masculinity.